MUHANDISLIK TA’LIMIDA INNOVATSIYALARNI QO‘LLASH AHAMIYATI - Ruziyev, I.S. (SCIENCE and SOCIETY, 2025)
This article analyzes the opinions of academic teachers about the concepts of pedagogical innovations, their use in the educational process and their impact on quality. The importance of their effective use is also analyzed in education.